EFFECTS OF SUPPLEMENTATION OF MARIGOLD (TAGETES ERECTA) OLEORESIN ON GROWTH, SURVIVAL AND PIGMENTATION OF ROSY BARB, PUNTIUS CONCHONIUS (HAMILTON) - T. D. JAGADEESH; H. SHIVANANDA MURTHY; S. V. SURENDRANATH; PREETHA PANIKKAR; N. MANJAPPA; V. MAHESH (The Bioscan, 2015)
The study was carried out for a period of 45 days to elucidate the effect of marigold oleoresin on growth, survival and pigmentation of rosy barb, Puntius conchonius. Fish with initial weights ranging from 0.44 g to 0.47 g were fed with test diets T0, T1, T2 and T3 supplemented with marigold oleoresin at levels 0, 60, 120 and 180 ppm respectively. At the end of the feeding trial the total carotenoid concentration in fish muscle found significantly higher (p < 0.05) in both male (3.92±0.01 μgg-1) and female (3.35±0.02 μgg-1) fishes fed diet incorporated with 120 ppm marigold oleoresin. Survival rate of fish significantly increased (p < 0.05) with the supplementation of marigold oleoresin in the diet, highest being in 120 ppm level (96.66±3.33 %). However, there was no significant effect observed in growth, feed conversion ratio and specific growth rate of the fishes. Carotenoid content analysis from whole fish revealed that incorporation of dietary carotenoid resulted in a significant increase in total carotenoid concentration. The study concluded that cheaper and natural colour enhancer diets for rosy barb can be prepared using marigold oleoresin at 120 ppm level.